Expression Study of NDUFS1, NDUFV1, and NDUFV2 in Schizophrenia and Paranoid Personality Disorder: - Hashemi, Mehrdad; Haghighatfard, Arvin; Salehi, Mitra; Saberi, Seyed Mehdi (Galen Medical Journal, 2022)
Background: Schizophrenia (SCZ) is a major psychiatric disorder with unclear etiology and biological diagnosis. Paranoid personality disorder (PPD) is a type-A personality disorder characterized by paranoia and generalized mistrust. The etiology and molecular mechanisms of SCZ and PPD are not clarified. The present study aimed to examine the expression alteration of three major genes of mitochondrial complex I in the peripheral blood of patients with SCZ and PPD, and its correlations with clinical features of patients, especially the five major personality traits. Materials and Methods: This case-control study was performed on 735 SCZ, 742 PPD, and 750 non-psychiatric individuals. The mRNAs level of NDUFS1, NDUFV1, and NDUFV2 were assessed using quantitative real-time polymerase chain reaction, and their correlations with psychiatric symptoms were assessed by the positive and negative syndrome scale and the brief psychiatric rating scale tests, as well as personality traits that were evaluated by NEO Five-Factor Inventory. Results: Findings showed significant overexpression of NDUFS1, NDUFV1, and NDUFV2 in patients with SCZ (P=0.001, P=0.002, and P=0.004, respectively) and PPD (P=0.001, P=0.003, and P=0.006, respectively) compared with non-psychiatrists. In addition, these genes were associated with positive psychiatric symptoms and neuroticism in SCZ (P=0.008) and PPD (P=0.01). Conclusion: Overexpression genes that encode subunits of complex I play an important role in SCZ and PPD etiology and severity of symptoms. It may bring evidence about the significant role of bioenergetics dysfunction in psychotic behaviors in different psychiatric situations.